Autoimmune musicogenic epilepsy associated with anti‐glutamic acid decarboxylase antibodies and Stiff‐person syndrome. Issue 1 (12th December 2019) - Jesus‐Ribeiro, Joana; Bozorgi, Alireza; Alkhaldi, Modhi; Shaqfeh, Mahmoud; Fernandez‐Baca Vaca, Guadalupe; Katirji, Bashar
Abstract: Epilepsy should be suspected in patients with Stiff‐person syndrome and new onset paroxysmal episodes. Musicogenic epilepsy may be a manifestation of anti‐GAD‐Ab spectrum, supporting an autoimmune workup in these patients. Appropriate treatment is not well established, and immunotherapy should be considered in patients with only partial response to antiepileptic drugs. Abstract : Epilepsy should be suspected in patients with Stiff‐person syndrome and new onset paroxysmal episodes. Musicogenic epilepsy may be a manifestation of anti‐GAD‐Ab spectrum, supporting an autoimmune workup in these patients. Appropriate treatment is not well established, and immunotherapy should be considered in patients with only partial response to antiepileptic drugs.